Natural product-based screening led to the discovery of a novel PXR agonist with anti-cholestasis activity - Huang Dong; Zhao Ying-yuan; Wang Rui-min; Li Wei; Yuan Fang-yu; Yan Xue-long; Yang Xiao; Tang Gui-hua; Yin Sheng; Bi Hui-chang (Acta Pharmacologica Sinica, 2022)
Cholestasis is a major cause of a series of bile flow malfunction-related liver diseases. Pregnane X receptor (PXR) is a key regulator in endo- and xeno-biotics metabolism, which has been considered as a promising therapeutic target for cholestasis. In this study we conducted human PXR (hPXR) agonistic screening using dual-luciferase reporter gene assays, which led to discovering a series of potent hPXR agonists from a small Euphorbiaceae diterpenoid library, containing 35 structurally diverse diterpenoids with eight different skeleton types. The most active compound 6, a lathyrane diterpenoid (5/11/3 ring system), dose-dependently activated hPXR with a high selectivity, and significantly upregulated the expression of hPXR downstream genes CYP3A4 and UGT1A1. In LCA-induced cholestasis mouse model, administration of compound 6 (50 mg· kg−1. d−1, ip) for 7 days significantly suppressed liver necrosis and decreased serum levels of AST, ALT, Tbili, ALP, and TBA, ameliorating LCA-induced cholestatic liver injury. We further revealed that compound 6 exerted its anti-cholestatic efficacy via activation of PXR pathway, accelerating the detoxification of toxic BAs and promoting liver regeneration. These results suggest that lathyrane diterpenoids may serve as a promising scaffold for future development of anti-cholestasis drugs.